Writing scientific software : a guide for good style - Oliveira, Suely; Stewart, David, 1961-; Cambridge eBooks (Cambridge : Cambridge University Press, 2006)
The core of scientific computing is designing, writing, testing, debugging and modifying numerical software for application to a vast range of areas: from graphics, meteorology and chemistry to engineering, biology and finance. Scientists, engineers and computer scientists need to write good code, for speed, clarity, flexibility and ease of re-use. Oliveira and Stewart's style guide for numerical software points out good practices to follow, and pitfalls to avoid. By following their advice, readers will learn how to write efficient software, and how to test it for bugs, accuracy and performance. Techniques are explained with a variety of programming languages, and illustrated with two extensive design examples, one in Fortran 90 and one in C++: other examples in C, C++, Fortran 90 and Java are scattered throughout the book. This manual of scientific computing style will be an essential addition to the bookshelf and lab of everyone who writes numerical software.
pt. I. Numerical software -- Why numerical software? -- Scientific computation and numerical analysis -- Priorities -- Famous disasters -- Exercises -- pt. II. Developing software -- Basics of computer organization -- Software design -- Data structures -- Design for testing and debugging -- Exercises -- pt. III. Efficiency in time, efficiency in memory -- Be algorithm aware -- Computer architecture and efficiency -- Global vs. local optimization -- Grabbing memory when you need it -- Memory bugs and leaks -- pt. IV. Tools -- Sources of scientific software -- Unix tools -- pt. V. Design examples -- Cubic spline function library -- Multigrid alogrithms.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Computer software -- Development; Software engineering; Science -- Data processing; Science -- Software; Electronic books